The Effect of holistic focus of attention on golf putting in expert - Seakhwan Shin; Taegyong Kwon (Korea Institute of Sport Science, 2020)
Purpose The purpose of this study is to investigate the effectiveness of the holistic focus of attention(H-FOA), presented as an alternative attention concept, to explore effective attention focus for the skilled performer. Methods KPGA's experts (N = 24) were selected and randomly assigned to external focus, overall focus and control groups. Experiments were conducted in the putting competition of the target distance (4m, 5m and 6m). Performance was measured for accuracy. Results Interestingly, the control group showed the high putting performance accuracy (MRE). In addition, the holistic focus of attention group was able to identify performance similar to the control group. The effect of external attention focus could not be confirmed. Conclusions Results of this study indicate that external focus may be unnecessary for skilled golfers. Rather, holistic focus of attention is highlighted for the improvement of players' attentional focus under pressure.